THE HISTORICAL SPACE AS A LIVING MUSEUM: A SITUATED AND HISTORICAL VIEW AS AN AXIS OF TEACHING INNOVATION. - ROCA, GUILLEM; GUTIÉREZ-UJAQUE, DANIEL (Imago Temporis. Medium Aevum, 2023)
This article presents the methodological proposal made during two academic years in the subject "Geography and History" of the degree in Social Education at the University of Lleida. An analysis of the old town was presented in the proposal, which was given a historical and social context. To reflect on current problems affecting the community of residents of the old town, we examined different spaces understood as open-air museums. The experience --which was part of the University of Lleida's call for the Improvement of University Education-- demonstrates the effectiveness of placing the spaces, together with their ]1istorical context, as protagonists of the historical narrative to encourage active learning that is compatible with the training requirements of students pursuing a degree in social education.